Heterogeneous Effects of Women’s Schooling on Fertility, Literacy and Work: Evidence from Burundi’s Free Primary Education Policy - Wild, Frederik; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2020)
This article investigates the effect of women’s schooling on fertility as well as on associated mechanisms by leveraging Burundi’s free primary education policy (FPE) of 2005 as a natural experiment.
Keywords: Child care; Children; Fertility; Income distribution; Sub-Saharan Africa; Youth; Education; Family planning; Migration; Economic development; Female Education; Human Development; Education Policy; Educational Influence; Child Development; Human Resources